Several Variables That Influence The Improvement of Work Productivity of MSME Employees in Batu City - Marsiana Klara Mbadhi; Indra Gunawan, Cakti; Willy Tri Hardiyanto (IRDH International Journal of Social Sciences & Humanities, 2026)
Batu City is one of the areas that implements MSME development. The purpose of this study is to analyze the influence of employee recruitment, salary provision, and incentives on employee work productivity in Batu City MSMEs, specifically UD Kerupuk Singkong Nusantara Putra. This research uses a quantitative method. The data analysis methods were multiple linear regression, partial t-test, and simultaneous F-test using SPSS 26. The t-test hypothesis results show that the Employee Recruitment variable (X1) has a significant effect on Employee Work Productivity (Y) at UD Kerupuk Singkong Nusantara Putra with a t-value of 2.371, Salary Provision (X2) has a significant effect on Employee Work Productivity (Y) with a t-value of 2.475, and Incentives (X3) have a significant effect on Employee Work Productivity (Y) with a t-value of 2.466, with all X variables (t-value > t-table = 2.055). The regression coefficient results show that X1 is 0.415, which has a positive effect; X2 is 0.503, which has a positive effect (the most dominant); and X3 is 0.443, which has a positive effect on variable Y. Therefore, all independent variables have a significant effect on the dependent variable, with the results indicating that Employee Recruitment (X1), Salary Provision (X2), and Incentives (X3) have a positive effect on Employee Work Productivity (Y) or influence by 62.5% (R2). These results prove that all independent variables are able to improve Employee Work Productivity for employees working in SMEs in Batu City, specifically at UD Kerupuk Singkong Nusantara Putra.